2012
DOI: 10.1148/radiol.12112263
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging–controlled Transurethral Ultrasound Therapy for Conformal Treatment of Prostate Tissue: Initial Feasibility in Humans

Abstract: MR imaging-controlled transurethral ultrasound therapy is feasible, safe, and well tolerated. This technology could be an attractive approach for whole-gland or focal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 58 publications
2
79
0
Order By: Relevance
“…6 Although the study confirmed preclinical findings, the timing of radical prostatectomy prevented interpretation of treatment related adverse events.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…6 Although the study confirmed preclinical findings, the timing of radical prostatectomy prevented interpretation of treatment related adverse events.…”
mentioning
confidence: 72%
“…1 ½F1 ). 6 A transurethral device delivers high intensity ultrasound directly into the prostate, quickly raising temperatures to the point of thermal coagulation. 7e10 MRI thermometry measurements acquired in real time during treatment are applied by a control algorithm to adjust the ultrasound output (power, frequency and rotation rate) and conform ablation volume the specific prostate geometry of the patient.…”
mentioning
confidence: 99%
“…Proof-of-principle studies have shown that real-time MRI-guided focused ultrasound can produce extensive coagulative necrosis with no residual tumor, excellent concordance with target zones, and postablation dynamic contrast-enhanced MRI [16,25]. Ahmed and colleagues [26] treated 41 patients with focused ultrasound planned with pretreatment MRI and TRUS mapping biopsy delivered without real-time MRI monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is performed under spinal or general anesthesia after insertion of a suprapubic catheter for continuous drainage of the urinary bladder. Chopra et al [59] reported the first proof-of-principle study demonstrating its safety and feasibility in eight patients for localized PCa. The treatment volume in this study was a 1808 sector of the posterior gland.…”
Section: Magnetic Resonance-guided Transurethral Focused Ultrasound Tmentioning
confidence: 99%